Detection of immunoglobulin M and immunoglobulin G antibodies to Mycoplasma pneumoniae in children with community-acquired lower respiratory tract infections - Surinder Kumar; Indu Bala Garg; Gulshan Rai Sethi; Sanchit Kumar; Sanjeev R Saigal (Wolters Kluwer Medknow Publications, 2018)
Context: Mycoplasma pneumoniae (M. pneumoniae) causes up to 40% of community-acquired pneumonia in children. It is impossible to identify M. pneumoniae infection on the basis of clinical signs, symptoms, and radiological features. Therefore, correct etiological diagnosis strongly depends on laboratory diagnosis. Aims: This study aims to investigate the role of M. pneumonia e in pediatric lower respiratory tract infections (LRTIs) employing enzyme-linked immunosorbent assays (ELISA) and particle agglutination (PA) test. Settings and Design: Two hundred and eighty children, age 6 months to 12 years with community-acquired LRTIs were investigated for M. pneumoniae etiology. Materials and Methods: We investigated 280 children hospitalized for community-acquired LRTIs, using ELISA and PA test for detecting M. pneumoniae immunoglobulin M (IgM) and immunoglobulin G antibodies. Statistical Analysis Used: The difference of proportion between the qualitative variables was tested using the Chi-square test and Fischer exact test. P ≤ 0.05 was considered as statistically significant. Kappa value was used to assess agreement between ELISA and PA test. Results: M. pneumoniae was positive in 51 (23.2%) <5 years and 33 (54.0%) children in ≥5 years of age group, and this difference was statistically significant (P < 0.001). Clinical and radiological findings in M. pneumoniae positive and negative groups were comparable. ELISA detected M. pneumoniae in 78 (27.8%) and PA test 39 (13.9%) patients; 33 (84.6%) ELISA positive and 6 (15.4%) ELISA negative. ELISA/PA test together detected M. pneumoniae infection in 84 (30%) children. Conclusions: Our data underline that M. pneumoniae plays an important role in children with community-acquired LRTIs and more particularly in children >5 years of age.